The moral psychology of rationing among physicians: the role of harm and fairness intuitions in physician objections to cost-effectiveness and cost-containment - Antiel, Ryan M (BioMed Central, 2013)
INTRODUCTION: Physicians vary in their moral judgments about health care costs. Social intuitionism posits that moral judgments arise from gut instincts, called “moral foundations.” The objective of this study was to determine if “harm” and “fairness” intuitions can explain physicians’ judgments about cost-containment in U.S. health care and using cost-effectiveness data in practice, as well as the relative importance of those intuitions compared to “purity”, “authority” and “ingroup” in cost-related judgments. METHODS: We mailed an 8-page survey to a random sample of 2000 practicing U.S. physicians. The survey included the MFQ30 and items assessing agreement/disagreement with cost-containment and degree of objection to using cost-effectiveness data to guide care. We used t-tests for pairwise subscale mean comparisons and logistic regression to assess associations with agreement with cost-containment and objection to using cost-effectiveness analysis to guide care. RESULTS: 1032 of 1895 physicians (54%) responded. Most (67%) supported cost-containment, while 54% expressed a strong or moderate objection to the use of cost-effectiveness data in clinical decisions. Physicians who strongly objected to the use of cost-effectiveness data had similar scores in all five of the foundations (all p-values > 0.05). Agreement with cost-containment was associated with higher mean “harm” (3.6) and “fairness” (3.5) intuitions compared to “in-group” (2.8), “authority” (3.0), and “purity” (2.4) (p < 0.05). In multivariate models adjusted for age, sex, region, and specialty, both “harm” and “fairness” were significantly associated with judgments about cost-containment (OR = 1.2 [1.0-1.5]; OR = 1.7 [1.4-2.1], respectively) but were not associated with degree of objection to cost-effectiveness (OR = 1.2 [1.0-1.4]; OR = 0.9 [0.7-1.0]). CONCLUSIONS: Moral intuitions shed light on variation in physician judgments about cost issues in health care.